Pengaruh reward, insentif, pembagian tugas dan pengembangan karier pada kepuasan kerja perawat di rumah sakit ortopedi Prof. Dr. R. Soeharso Surakarta - suhartono, jimmy fitria; Sawitri, Hunik Sri Runing (Universitas Muhammadiyah Surakarta, 2017)
The purpose of this study to analyze the influence of rewards, incentives, job and career development in the job satisfaction of nurses. This study was included in the category of ex-post facto research. This study uses the individual (individual) for the unit of analysis, answer questions based on the responses of each individual (nurse Orthopaedic Hospital Prof. Dr. R. Soeharso Surakarta). The data used is primary and secondary data. The population in this study were nurses working in the Field of Nursing totaling 187 people and taken samples of 65 people with accidental sampling technique. The research instrument used a questionnaire with Likert scale. The data analysis includes validation test, reliability and multiple regression analysis. Test model assumptions including normality test, autocorrelation, multicollinearity and heteroscedasticity.The results showed that reward positive and significant impact on job satisfaction of nurses, incentives positive and significant impact on job satisfaction of nurses, division of positive and significant impact on job satisfaction of nurses, career development positive and significant impact on job satisfaction of nurses, and the rewards, incentives , division tuags and career development have a significant effect on job satisfaction of nurses at the hospital. Orthopedics Prof. Dr. R. Soeharso Surakarta.